2009
DOI: 10.1161/circulationaha.108.815621
|View full text |Cite
|
Sign up to set email alerts
|

Improved Patient Survival Using a Modified Resuscitation Protocol for Out-of-Hospital Cardiac Arrest

Abstract: Background-Cardiac arrest continues to have poor survival in the United States. Recent studies have questioned current practice in resuscitation. Our emergency medical services system made significant changes to the adult cardiac arrest resuscitation protocol, including minimizing chest compression interruptions, increasing the ratio of compressions to ventilation, deemphasizing or delaying intubation, and advocating chest compressions before initial countershock. Methods and Results-This retrospective observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 55 publications
3
77
0
4
Order By: Relevance
“…5) in each area in which it was instituted; first in Rock and Walworth counties (WI, USA), in Kansas City (MO, USA), and in Arizona 39, 48, 49, 50…”
Section: Cardiocerebral Resuscitation Improved Survivalmentioning
confidence: 99%
“…5) in each area in which it was instituted; first in Rock and Walworth counties (WI, USA), in Kansas City (MO, USA), and in Arizona 39, 48, 49, 50…”
Section: Cardiocerebral Resuscitation Improved Survivalmentioning
confidence: 99%
“…27 Evidence from studies of minimally interrupted cardiac resuscitation and cardiocerebral resuscitation supports the new decreased emphasis on pulse checks to promote continuous CPR with minimal interruptions. 28,29 Beyond the timing of ventilation, care must be taken to avoid excessive ventilation. Observational studies on human cardiac arrest patients have documented this to be a pervasive problem, one that should be considered in the context of animal models of cardiac arrest that demonstrate that excessive ventilation translates to poorer hemodynamics and survival.…”
Section: Airway and Breathingmentioning
confidence: 99%
“…77,78 More pertinent to patients experiencing SCD is work demonstrating biphasic waveforms to be equivalent or superior to monophasic waveforms in defibrillating to an organized rhythm. 28,79 However, evidence is lacking on improved survival in OHCA resulting from the implementation of biphasic defibrillation.…”
Section: Defibrillator Sequence Technique and The Use Of Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome was reported to be worsened when AAM with ET was performed in cases of OHCA with shockable rhythms [5,6]. Recently, Garza et al reported that avoidance of tracheal intubation as an early airway management and an increase in the ratio of chest compression to ventilation improved survival rate in OHCA of cardiac origin [6].In Japan, certified paramedics who have completed training programs for tracheal intubation have used ET in patients with OHCA since July 2004. The program includes 180 hours of lectures and exercises in schools as well as experience with 30 cases in hospital operating rooms.…”
mentioning
confidence: 99%